1994
DOI: 10.1084/jem.179.1.305
|View full text |Cite
|
Sign up to set email alerts
|

Continuous administration of anti-interleukin 10 antibodies delays onset of autoimmunity in NZB/W F1 mice.

Abstract: We have previously shown that continuous administration of anti-interleukin 10 (anti-IL-10) antibodies (Abs) to BALB/c mice modifies endogenous levels of autoantibodies, tumor necrosis factor alpha (TNF-alpha), and interferon gamma, three immune mediators known to affect the development of autoimmunity in "lupus-prone" New Zealand black/white (NZB/W)F1 mice. To explore the consequences of IL-10 neutralization in NZB/W F1 mice, animals were injected two to three times per week from birth until 8-10 mo of age wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
278
1
7

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(309 citation statements)
references
References 29 publications
23
278
1
7
Order By: Relevance
“…In contrast, continuous administration of IL-10 exacerbated GN in the New Zealand black/ white mouse model of lupus, which is classified as a Th2-predominant model. 3,36 Many factors complicate the pathogenesis of kidney diseases. To test the involvement of the many recognized candidate genes quickly, the development of a gene transfer method is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, continuous administration of IL-10 exacerbated GN in the New Zealand black/ white mouse model of lupus, which is classified as a Th2-predominant model. 3,36 Many factors complicate the pathogenesis of kidney diseases. To test the involvement of the many recognized candidate genes quickly, the development of a gene transfer method is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of IL-10 and IL-6, as well as the associated cytokines TNF-a and GM-CSF, could enhance B-cell proliferation and differentiation [16][17][18][19]. Exogenous IL-6 has been shown to promote murine lupus, while specific monoclonal antibodies (MoAb) to IL-6 and IL-10 delay the development of this disease in NZB/W F 1 mice [20,21]. An intrinsic overproduction of these cytokines might also explain the pre-existing B-cell hyperactive state reported in family members of SLE patients, as well as in lupus patients themselves [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in our understanding of the biology of cytokines have shed new light on the mechanisms underlying this inappropriate antibody production. Thus, it was demonstrated that IL-10 is overexpressed in lupus patients [1,2] and mediates, at least in part, the excessive immunoglobulin production and the autoantibody response associated with human and murine SLE [3,4]. Such results demonstrate that cytokines are closely involved in the pathogenesis of lupus and suggest that cytokine manipulation might be useful for the control of the disorder.…”
Section: Introductionmentioning
confidence: 99%